1999
DOI: 10.1021/ol990229n
|View full text |Cite
|
Sign up to set email alerts
|

Five-Membered-Ring 9-I-2 Radicals:  Direct Detection and Comparison with Other Hypervalent Iodine Radicals

Abstract: Photolysis of 1,4-diiodo-1,4-diphenylbutane leads to a five-membered-ring 9-I-2 radical (6b), whose absorption spectrum and stability are compared with those of other hypervalent iodine radicals of different ring size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Two-laser two-color flash photolysis of these diiodoalkanes has been performed using 266 nm pulses to produce the cyclic hypervalent 9-I-2 iodine radicals, and a second laser pulse (nitrogen laser at 337 nm or excimer laser at 308 nm) has been used to irradiate them. A permanent and irreversible bleaching of the signal of the cyclic hypervalent 9-I-2 iodine radicals is concomitant with the formation of more RI 2 - - -I • complex (Figure and insets), which agrees with the photoextrusion of iodine atom from the cyclic hypervalent radical. Product studies on the photolysis of 1, n -diiodo-1, n -diphenylalkanes under high-intensity irradiation conditions have shown the formation of products that can be considered fingerprints for the intermediacy of the corresponding 1, n -diphenyl-1, n -alkanediyl biradicals.…”
Section: Photochemistry Of 1n-dihaloalkanes (N > 2):  Bichromophores ...supporting
confidence: 70%
See 1 more Smart Citation
“…Two-laser two-color flash photolysis of these diiodoalkanes has been performed using 266 nm pulses to produce the cyclic hypervalent 9-I-2 iodine radicals, and a second laser pulse (nitrogen laser at 337 nm or excimer laser at 308 nm) has been used to irradiate them. A permanent and irreversible bleaching of the signal of the cyclic hypervalent 9-I-2 iodine radicals is concomitant with the formation of more RI 2 - - -I • complex (Figure and insets), which agrees with the photoextrusion of iodine atom from the cyclic hypervalent radical. Product studies on the photolysis of 1, n -diiodo-1, n -diphenylalkanes under high-intensity irradiation conditions have shown the formation of products that can be considered fingerprints for the intermediacy of the corresponding 1, n -diphenyl-1, n -alkanediyl biradicals.…”
Section: Photochemistry Of 1n-dihaloalkanes (N > 2):  Bichromophores ...supporting
confidence: 70%
“…Laser flash photolysis of 1, n -diiodo-1, n -diphenylalkanes (deaerated cyclohexane solutions), using either a Nd:YAG laser (266 nm) or a XeCl excimer laser (308 nm), leads to the formation of two transients with low reactivity toward oxygen (for the 1,4-diiodo-1,4-diphenylbutane, see Figure and insets). One of them has been assigned to the cyclic hypervalent 9-I-2 iodine radical (Scheme ) with absorption maxima and lifetime depending on the ring size; its nature and behavior are due to spin delocalization in the n -iodoalkyl radicals with participation of the remaining iodine atom.…”
Section: Photochemistry Of 1n-dihaloalkanes (N > 2):  Bichromophores ...mentioning
confidence: 99%
“…14 They are known to decompose almost instantaneously to an alkyl radical and an alkyl iodide. 15 The alkyl radical 10 formed in this manner may be a good enough oxidant 16 to oxidize the ate-complex 5 to the dialkyliodinanyl radical 9, with concomitant formation of the Grignard reagent 6.…”
mentioning
confidence: 99%
“…It has been demonstrated that, indeed, five-membered cyclic 9-I-2 species are more stable than other I-centered radicals. 62 Radical polymerizations initiated by other (acyclic) HV iodine compounds, such as (diacetoxyiodo)benzene, have also been shown to have some of the characteristics of "living" polymerizations. 63,64 Studies of the role www.soci.org R Kumar et al…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that polymerizations of MMA in the presence of BIO‐Cl proceed for periods exceeding 10 half‐life times of the initiator, which suggests that in these reaction systems, at least some chains are "living" – plausibly formed by reversible capping of the propagating radicals with the 9‐I‐2 (iodanyl) radicals. It has been demonstrated that, indeed, five‐membered cyclic 9‐I‐2 species are more stable than other I‐centered radicals 62 . Radical polymerizations initiated by other (acyclic) HV iodine compounds, such as (diacetoxyiodo)benzene, have also been shown to have some of the characteristics of “living” polymerizations 63,64 .…”
Section: Resultsmentioning
confidence: 99%